A Fuzzy Logic PI Trajectory Following Control in a Chaotically Loaded Real Mechatronic Dynamical System with Stick-Slip Friction - Kunikowski, Wojciech; Olejnik, Paweł; Awrejcewicz, Jan (Journal of Vibration Testing and System Dynamics, 2026)
Fuzzy logic control algorithms are regarded to as a relatively new concept in modern control theory. This paper presents a comparative analysis of two qualitatively different approaches used for angular velocity control of a DC motor subject to chaotic disturbances coming from a gear with a transmission belt carrying a vibrating load. The purpose is to achieve accurate control of speed of the DC motor (a plant), especially, when the motor parameters and some external loading conditions are partially unknown. First, the classical approach based on the PID control is considered, and then a fuzzy logic based alternative is proposed. Two different controllers are developed, i.e. the classical PID controller and a Mamdani type fuzzy logic PI controller. Both control algorithms are implemented on an 8-bit AVR ATmega644PA microcontroller. Based on step responses of the plant, an analysis as well as an interesting comparison of the controllers’ performance has been presented.